Long-term outcomes of the pentaspline pulsed-field ablation catheter for the treatment of paroxysmal atrial fibrillation: results of the prospective, multicentre FARA-Freedom Study - Metzner, Andreas; Fiala, Martin; Vijgen, Johan; Ouss, Alexandre; Gunawardene, Melanie; Hansen, Jim; Kautzner, Josef; Schmidt, Boris; Duytschaever, Mattias; Reichlin, Tobias; Blaauw, Yuri; Sommer, Philipp; et al. (Europace, 2024)
AIMS: Pulmonary vein isolation (PVI) is a well-established strategy for the treatment of paroxysmal atrial fibrillation (PAF). Despite randomized controlled trials and real-world data showing the promise of pulsed-field ablation (PFA) for this treatment, long-term efficacy and safety data demonstrating single-procedure outcomes off antiarrhythmic drugs remain limited. The aim of the FARA-Freedom Study was to evaluate the long-term efficacy and safety of PFA using the pentaspline catheter for PAF. METHODS AND RESULTS: FARA-Freedom, a prospective, non-randomized, multicentre study, enrolled patients with PAF undergoing de novo PVI with PFA, who were followed for 12 months with weekly transtelephonic monitoring and a 72-h Holter ECG at 6 and 12 months. The primary safety endpoint was a composite of device- or procedure-related serious adverse events out to 7 days post-ablation and PV stenosis or atrioesophageal (AE) fistula out to 12 months. Treatment success is a composite of acute PVI and chronic success, which includes freedom from any documented atrial tachyarrhythmia longer than 30 s, use of antiarrhythmic drugs or cardioversion after a 3-month blanking period, or use of amiodarone or repeat ablation at any time. The study enrolled 179 PAF patients (62 ± 10 years, 39% female) at 13 centres. At the index procedure, all PVs were successfully isolated with the pentaspline PFA catheter. Procedure and left atrial dwell times, with a 20-min waiting period, were 71.9 ± 17.6 and 41.0 ± 13.3 min, respectively. Fluoroscopy time was 11.5 ± 7.4 min. Notably, monitoring compliance was high, with 88.4 and 90.3% with weekly events and 72-h Holter monitors, respectively. Freedom from the composite primary effectiveness endpoint was 66.6%, and 41 patients had atrial tachyarrhythmia recurrence, mostly recurrent atrial fibrillation (31 patients). The composite safety endpoint occurred in two patients (1.1%), one tamponade and one transient ischaemic attack. There was no coronary spasm, PV stenosis, or AE fistula. There were four cases of transient phrenic nerve palsy, but all resolved during the index procedure. CONCLUSION: In this prospective, non-randomized, multicentre study, PVI using a pentaspline PFA catheter was effective in treating PAF patients despite rigourous endpoint definitions and high monitoring compliance and demonstrated favourable safety. REGISTRATION: Clinical Trials.gov Identifier: NCT05072964 (sponsor: Boston Scientific Corporation).
Keywords: Pulmonary Veins; Prospective Studies; venae pulmonales; Humans; Constriction, Pathologic; Recurrence; prospektivní studie; fibrilace síní; Fistula; Anti-Arrhythmia Agents; mužské pohlaví; antiarytmika; stenóza; tachykardie; katetrizační ablace; výsledek terapie; recidiva; Treatment Outcome; ženské pohlaví; Catheter Ablation; Tachycardia; lidé; Atrial Fibrillation; píštěle; Male; Female